STUDY OF GOVERNMENT FUNCTION AND BUSINESS FUNCTION OF BONTO BAHARI FISH LANDING BASE (PPI) IN BONTOA DISTRICT MAROS REGENCY SOUTH SULAWESI - Ashilah Muthiah Usman; Achmar Mallawa; Ilham Jaya (Hasanuddin University, 2024)
This research aims to (1) Identify the functions of PPI that running as its function according to PER.08/MEN/2012, (2) calculated the functioning rate according to PER.08/MEN/2012. This research was conducted in November until December 2021 at PPI Bonto Bahari, Bontoa District, Maros regency, South Sulawesi province. The method in this research used a case study method through direct observation of the activities at PPI by collected primary and secondary data obtained by using observation, interview and questionnaire filling. Identification function was analyzed by descriptively the function rate was analyzed by using a scoring method. So the results are (1) for the function of government there are only three of ten functions are implemented is catch & fishery data collection, supervision and control of fish resources and monitoring of coastal areas and business function there are only four of nine functions are implemented is mooring services, utilization of land and facilities, fish loading and unloading services, and marketing and distribution of fish, (2) The functioning rate for ten government functions is 28% suitability value, for nine business functions is 40% suitability value, these two functions are included in the category of 50% non-functioning. The conclusion is that the government function and the business function at PPI Bonto Bahari Maros Regency are not running generally as its function.